2009
DOI: 10.3791/1182
|View full text |Cite
|
Sign up to set email alerts
|

Processing the Loblolly Pine PtGen2 cDNA Microarray

Abstract: PtGen2 is a 26,496 feature cDNA microarray containing amplified loblolly pine ESTs. The array is produced in our laboratory for use by researchers studying gene expression in pine and other conifer species. PtGen2 was developed as a result of our gene discovery efforts in loblolly pine, and is comprised of sequences identified primarily from root tissues, but also from needle and stem. 1,2 PtGen2 has been tested by hybridizing different Cy-dye labeled conifer target cDNAs, using both amplified and non-amplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The hybridization reference sample consisted of a pool containing equal amounts of total RNA from all five time points investigated. Fluorescent labelling, hybridization, pre- and post-hybridization washes, scanning, and data processing were performed according to Lorenz et al [ 86 ], except that 2 μg of Cy-labeledamplified RNA was used to hybridize with the array after fragmentation using Fragmentation Reagent (Ambion, Cat. #AM8740).…”
Section: Methodsmentioning
confidence: 99%
“…The hybridization reference sample consisted of a pool containing equal amounts of total RNA from all five time points investigated. Fluorescent labelling, hybridization, pre- and post-hybridization washes, scanning, and data processing were performed according to Lorenz et al [ 86 ], except that 2 μg of Cy-labeledamplified RNA was used to hybridize with the array after fragmentation using Fragmentation Reagent (Ambion, Cat. #AM8740).…”
Section: Methodsmentioning
confidence: 99%
“…Microarray processing and hybridization protocols have been described previously [ 36 , 45 ]. Slides were incubated in a HybChamber™ (Genomic Solutions, Ann Arbor, MI) containing 20 uL 100 mM DTT in the humidity wells.…”
Section: Methodsmentioning
confidence: 99%
“…Towards this objective we developed a collection of public genomics tools, including a set of ca. 172,000 Sanger ESTs from mostly root tissues, an annotated 26496-feature cDNA microarray for pine (PtGen2), and optimized protocols for microarray analysis of pine tissues [ 32 , 34 - 36 ]. After validating the PtGen2 microarray, we identified 2445 genes that are differentially expressed in drought-stress roots from P. taeda and demonstrated that the transcript population in P. taeda roots returns to the pre-drought state within 48 hours of cessation of the drought treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The CTAB/LiCl method described by Chang and colleagues (1993) was able to recover good quality RNA from root samples of P. taeda; however, the quantity of recovered RNA was relatively low (∼ 6 ηg RNA mg −1 root cluster). Several CTAB methods modified from Chang and colleagues (1993) or Liao and colleagues (2004) were applied to extract RNA from larger amount of pine tissues (1-4 g) (Joosen et al, 2006;Lorenz et al, 2009;Canales et al, 2011). In this study, we modified the RNA extraction method from Chang and colleagues (1993) combined with genome grinding/beading strategy to homogenize small amounts of root tissue.…”
Section: Sampling and Rna Extraction For Field-collected Samplesmentioning
confidence: 99%